UPAYA PENCEGAHAN TINDAK PIDANA TERORISME OLEH DIREKTORAT INTELIJEN KEAMANAN DI KEPOLISIAN DAERAH RIAU - Nurhediansyah, Redyka; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In the development of today's society, along with the increasing development of technology, transportation, information and communication, so that it has an impact on the pattern of people's lives. These developments not only have a positive impact but have a negative impact, such as the behavior of irregularities in society, namely acts of terror or terrorism. The Police have an Intelligence Directorate in charge of maintaining security. The Directorate of Intelligence Security as part of the dynamic structure of police activities has an important and strategic role in helping to prevent terrorism. The purpose of this thesis is to know the Terrorism Crime Prevention Efforts by the Directorate of Regional Security Intelligence in the Riau Regional Police. This research is sociological or empirical research, namely the type of research that uses community assumptions in looking for facts that occur in the field to answer an existing problem. This research was conducted in the jurisdiction of the Riau Regional Police. while the population and sample are parties related to the problems examined in this study, the data sources used, primary data, secondary data, and tertiary data. The technique of collecting data in this study was through interviews and literature review. From the results of the research the authors concluded, first the role of the Directorate of Security Intelligence in Efforts to prevent terrorism in the Riau Regional Police, namely conducting investigations by providing information or information material called intel products to the User. in the form of information reports, special information, and assignment report. Terrorism Crime Prevention Efforts by the Directorate of Security Intelligence in the Riau Regional Police are by pre-emptive or preventive measures, prevention efforts that are carried out are to deal with former terrorism prisoners and early detection of groups that can fall prey to terrorism groups, related agencies such as the National Counterterrorism Agency and Detachment 88 also cooperates with each other in efforts to prevent terrorism by actively disseminating the dangers of terrorism to the public. It is expected that all law enforcement agencies will be more maximal in making prevention efforts against these crimes, by increasingly conducting counseling on the dangers of terrorism. The relevant government must also coordinate with relevant institutions engaged in counter-terrorism efforts so that the solutions to the obstacles encountered by field personnel can be found together.Keywords: Ditintelkam - Police - Prevention - Terrorism